O31 Integrative analysis reveals a molecular stratification of systemic autoimmune diseases. (23rd March 2020) - Barturen, Guillermo; Babaei, Sepideh; Català-Moll, Francesc; Martínez-Bueno, Manuel; Makowska, Zuzanna; Martorell-Marugán, Jordi; Carmona-Sáez, Pedro; Toro-Domínguez, Daniel; Carnero-Montoro, Elena; Kerick, Martin; Acosta-Herrera, Marialbert; Lann, Lucas Le; et al.
Abstract : Background: Clinical heterogeneity, a hallmark of systemic autoimmune diseases (SADs) impedes early diagnosis and effective treatment, issues that may be addressed if patients could be grouped into a molecular defined stratification. Methods: With the aim of reclassifying SADs independently of the clinical diagnoses, unsupervised clustering of integrated whole blood transcriptome and methylome cross-sectional data of 918 patients with 7 SADs and 263 healthy controls was undertaken. An inception cohort prospectively followed for 6 and 14 months was studied to validate the results in early cases and analyze if cluster assignment was modified with time. Results: Four clusters were identified: Three aberrant clusters were 'acute phase inflammatory', 'T cell immunity', and 'interferon', each including all diagnoses, were defined by genetic, clinical, serological and cellular features. A fourth cluster showed no specific molecular pattern, to which 74% of healthy controls clustered with patients. The inception cohort showed that most patients were either assigned always to the same cluster or moved from the healthy-like cluster to a single aberrant cluster resembling the relapsing-remitting dynamic of these diseases, showing that single aberrant molecular signatures characterize each individual patient. Conclusions: Patients with SADs share molecular signatures and can be therefore stratified into three disease clusters differentiating each patient into a specific molecular disease pathway. Such assignment is stable with time. These results have important implications for understanding disease progression and therapy design marking a paradigm shift in our view of SADs. Acknowledgment: This work has been supported through a grant from the Innovative Medicines Initiative Joint Undertaking No. 115565 and in-kind and in-cash contributions from the EFPIA partners. G.B. is supported by the Instituto de Salud Carlos III (ISCIII, Spanish Health Ministry), through the Sara Borrell subprogram (CD18/00153). The authors would like to particularly express their gratitude to the patients, nurses and many others who helped directly or indirectly in the consecution of this study.